Diagnostic yield and variant reassessment in the genes encoding Nav1.5 channel in Russian patients with Brugada syndrome - Zaklyazminskaya, Elena; Shestak, Anna; Podolyak, Dmitry; Komoliatova, Vera; Makarov, Leonid; Novitskaya, Anna; Revishvili, Amiran (Frontiers in Pharmacology, 2022)
Brugada syndrome (BrS) is an inherited cardiac arrhythmia characterized by ST-elevation, negative T-wave, and a high risk of sudden cardiac death (SCD) due to ventricular tachycardia. It is associated with mutations in over 20 genes but only SCN5A is recommended for routine genetic screening. This study was performed to estimate diagnostic yield and pathogenicity assessment of rare genetic variants in the genes encoding Nav1.5 channel in Russian patients with Brugada syndrome (BrS). Targeted genes panel sequencing of the 5 genes were screened using IonTorrent PGM with following Sanger confirmation. Detailed clinical evaluation of 75 unrelated BrS probands with a deep phenotyping of SCN5A(+) probands was performed. Twelve rare genetic variants (6 missense, 6 truncating) were initially identified and classified as disease-causing. Reassessment of the clinical significance in the light of the current guidelines revealed: 2 Pathogenic (P) variants; 8 Likely Pathogenic (LP); two missense variants (p.G274S and p.S1778H) were re-classified later as a variant of unknown significance (VUS). Unique VUS (p.Arg100Ser) was detected in the SCN4B gene. Lone Brugada-pattern was observed in 46% probands; 54% patients had concomitant arrhythmias. PR interval, the only electrocardiography parameter correlating with SCN5A-mutation, was longer (207 ± 24 ms) than normal in SCN5A(+)-probands. SCD cases were registered in 31 families. Depression was the only recurring extra-cardiac complaint in SCN5A(+) probands; it was self-reported in five SCN5A(+) probands, and co-segregated with Brugada pattern in 2 families. After variants reassessment, the ratio of SCN5A (+) probands with Brugada syndrome account for 13% in Russian cohort.